ChemInform Abstract: Decarboxylative Cascade Reactions of Dihydroxyfumaric Acid: A Preparative Approach to the Glyoxylate Scenario. Issue 44 (13th October 2016) - Richter, Celin; Berndt, Falko; Kunde, Tom; Mahrwald, Rainer
Abstract: The presented direct decarboxylative aldol reaction provides shortcuts for existing multistep routes to hydroxyketone structures found in natural products.